Development of a duplex real-time recombinase aided amplification assay for the simultaneous and rapid detection of PCV3 and PCV4 - Renjie Sun; Hanze Liu; Siqi Sun; Yating Wang; Ying Shan; Xiaoliang Li; Weihuan Fang; Yongle Yang; Ronghui Xie; Lingyan Zhao (Virology Journal)
Abstract Background Porcine circoviruses 3 (PCV3) and 4 (PCV4) are emerging pathogens with global implications for swine industry, disturbing the diagnosis of PCVs associated diseases due to a range of similar clinical symptoms and increasingly coinfections. A rapid and accurate method for detection of PCV3 and PCV4 is critical for controlling the transmission of associated disease. Methods We developed a duplex real-time recombinase aided amplification (RAA) assay for detection of both PCV3 and PCV4 simultaneously. The assay was completed within 20 min at 39℃ with the designed optimal primers and probes. Results The established assay was more convenient and simpler operation compared with conventional molecular biological assays. The assay achieved a detection limit of 73.67 copies/reaction for each circovirus (at 95% probability by probit regression analysis) and showed high specificity and no cross-reactivity with other important porcine viruses (including PCV2). The intra- and inter-group coefficients of variation (CV) were ranged from 2.08 to 4.97%, indicating high stability and reliability. Comparative analysis with PCV3 and PCV4 qPCR on 60 clinical samples and artificially spiked samples indicated high congruence (the kappa value was 0.966 and 1, respectively, with p < 0.001), with only minor discrepancies, validating effectiveness of the duplex RAA assay in detecting co-infections and its suitability for preliminary clinical diagnosis of PCV3 and PCV4. Conclusions This study provides a robust basis for multiplex detection of veterinary pathogens using RAA technique, enhancing the field’s capacity to control PCV3 and PCV4, and supporting reliable aid for epidemiological understanding of emerging circoviruses.